The Implementation of Mediated Instruction of Text (MIT) Strategy on Improving Reading Comprehension of Eighth Grade Students at Madrasah Tsanawiyah (Mts) Darul Amanah Teluk - Sylfana Ryan Mulia; Rosmen Rosmen; Fernando De Napoli Marpaung (Universitas KH. Abdul Chalim Mojokerto, 2026)
This classroom action research is aimed at analysing the impact of the Mediated Instruction of Text (MIT) strategy on the reading comprehension of eighth-grade students at MTs Darul Amanah Teluk. Focusing specifically on descriptive text comprehension, the study involves 24 students and employed a pre-test and post-test design. Data analysis using gain scores reveal a significant improvement in reading comprehension, with the average score increasing from 39.2 on the pre-test to 93.3 on the post-test. This gain of approximately 54 points indicates a substantial positive effect of the MIT strategy on students' reading abilities. Based on these findings, it is recommended that English teachers at MTs Darul Amanah Teluk integrate the MIT strategy into their reading instruction to enhance students' comprehension skills.